The Unruh effect and oscillating neutrinos. Issue 4 (April 2016) - Ahluwalia, Dharam Vir; Labun, Lance; Torrieri, Giorgio
Abstract: We give an overview of the issues and ambiguities associated with the Unruh effect, and argue that, as well as a very interesting phenomenon, it can also be used as a probe of fundamental physics. In particular, We point out that, because the detectable neutrino is not a mass Eigenstate, the Unruh effect works in a qualitatively different way than for any inertial process. For inertial processes, neutrinoes are produced as charged eigenstates, rather than as mass Eigenstates as in the comoving frame. This makes the Unruh effect detectable in microscopic processes, via, for example, $p→ nl^+\bar{ν}_l$ decays. Such an experiment would be invaluable both as a tool to measure neutrino masses and mixing angles, and to investigate the fundamental quantization of fields.